2022
DOI: 10.1002/ajoc.202200638
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Efficient SynthesisofFluorene and Indenoarene Carboxylates from Biaryldiazoacetates via BlueLight‐promoted Intramolecular CarbeneC−H Insertion

Abstract: Inspired by the recent discovery that aryldiazoacetates could be excited with visible light to generate carbenes in a mild and catalyst‐free manner, we tested the possibility to induce the cyclization of fluorenes from biaryldiazoacetate precursors simply by visible light irradiation at ambient temperature. The experimental results showed that 455 nm blue light is most effective on the synthesis of a diversity of fluorenes and indenoarenes in excellent yields. Analysis of UV absorbance and electronic transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Therefore, searching for greener synthesis of fluorenes under mild reaction conditions has become an urgent need. Our present approach to fluorenes is based on visible light‐induced photochemical reaction of diazo compounds that features mild reaction conditions (generated at ambient temperature in the absence of any transition metal catalysts), rendering it safer and more environmentally friendly compared to the traditional methods [52] (Scheme 1B). The current work was conducted as part of our ongoing research into green and sustainable orgainc transformations [53–56] .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, searching for greener synthesis of fluorenes under mild reaction conditions has become an urgent need. Our present approach to fluorenes is based on visible light‐induced photochemical reaction of diazo compounds that features mild reaction conditions (generated at ambient temperature in the absence of any transition metal catalysts), rendering it safer and more environmentally friendly compared to the traditional methods [52] (Scheme 1B). The current work was conducted as part of our ongoing research into green and sustainable orgainc transformations [53–56] .…”
Section: Methodsmentioning
confidence: 99%
“…Later, Sun and coworkers extended this intramolecular strategy to C(sp 2 )−H bonds, which allowed for preparation of fluorene derivatives 20.4 (Scheme 20b). 59 Very recently, Hari's group demon-strated the efficient synthesis of various spiro-β-lactones and lactams 20.6 using this photochemical approach (Scheme 20c). 60 In 2021, Koenigs and co-workers employed diaryl diazo compounds 21.1 in photochemical intermolecular C−H insertion reactions with alkynes 21.2 (Scheme 21).…”
Section: Cyclopropanation Cyclopropanation Of C−cmentioning
confidence: 99%
“…In the same report, the authors also found that this reaction can be performed intramolecularly with C­( sp 3 )–H to afford 5-membered lactone 20.2 (Scheme a). Later, Sun and co-workers extended this intramolecular strategy to C­( sp 2 )–H bonds, which allowed for preparation of fluorene derivatives 20.4 (Scheme b) . Very recently, Hari’s group demonstrated the efficient synthesis of various spiro-β-lactones and lactams 20.6 using this photochemical approach (Scheme c) …”
Section: Diazo Compounds As Singlet Carbene Precursorsmentioning
confidence: 99%